If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -7x + 2x = 3 Combine like terms: -7x + 2x = -5x 3 + -5x = 3 Add '-3' to each side of the equation. 3 + -3 + -5x = 3 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 3 + -3 -5x = 3 + -3 Combine like terms: 3 + -3 = 0 -5x = 0 Solving -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = 0 Simplifying x = 0
| 3(x+2)+1=6x-3(-3+x) | | -4=7x+10 | | 2x-8x+1=9 | | 558766745+x=88888888888888888888 | | 49=x+1+3x | | -40-(2x+5)=61 | | 2y^2+7y+10=[y+4] | | 6=7+(k/6) | | 4x+10=0 | | -2+2x=22 | | a^3-a^2b-ab^2+b^3=0 | | (18+x)+x=98 | | 19=-6y | | 4y-37=6y+13 | | 2(x-6)+6=4x-4 | | 6=7+k/6 | | y=2.5x+8 | | -2(7x-1)+1=-14x+3 | | 3x+3=240 | | 2x=3+4x+5 | | 7x-6-2x=29 | | 5x-3x+2=8 | | 4(9-x)=24 | | 2(2x+3)-3(x-5)=4 | | 10x-8=40x+10 | | (7x+8)=(9x-4) | | 8x-3=8(x-5) | | -4(1-3p)=-4-2(-p-5) | | x/4=11 | | 12x-83=6x+121 | | -(3x-7)=24 | | 2v-5=-10 |